Analysis of the melting, burning and flame spread of polymers with the particle finite element method - Oñate, Eugenio; Marti, Julio; Ryzhakov, Pavel; Rossi, Riccardo; Idelsohn, Sergio R. (Computer Assisted Methods in Engineering and Science, 2013)
A computational procedure for analysis of the melting, burning and flame spread of polymers under fire conditions is presented. The method, termed particle finite element method (PFEM), combines concepts from particle-based techniques with those of the standard finite element method (FEM). The key feature of the PFEM is the use of an updated Lagrangian description to model the motion of nodes (particles) in the thermoplastic material. Nodes are viewed as material points which can freely move and even separate from the main analysis domain representing, for instance, the effect of melting and dripping of polymer particles. A mesh connects the nodes defining the discretized domain where the governing equations are solved using the FEM. An incremental iterative scheme for the solution of the nonlinear transient coupled thermal-flow problem, including radiation, loss of mass by gasification and combustion is used. Examples of the possibilities of the PFEM for the modelling and simulation of the melting, burning and flame spread of polymers under different fire conditions are described.